PATHOLOGICAL STUDY OF LOCALLY ISOLATED FOWL POXVIRUS -EXPERIMENTALLY INFECTED TRACHEA USING SCANNING ELECTRON MICROSCOPY - Al-Hyali, H. M.; Al-Jumily, A. (The Iraqi Journal of Veterinary Medicine, 2021)
In this study fowl poxvirus has been isolated from naturally infected birds. This virus induced respiratory distress, 2, 3 and 4 days post inoculation, in intratracheally inoculated 8 week old chickens, these respiratory distress include congestion of tracheal mucosa, increased tracheal secreation and whitish-yellowish pastules appeared at ninth day post inoculation in the upper part of the trachea forming diphtheritic or pseudodiphtheritic membrane. Using scanning electron microscopy to study the changes that occurs in the epithelial surface of trachea. It was found that the virus causes proliferation of epithelial cells forming cluster like papilloma, deciliation and activation of goblet cells.